2008
DOI: 10.4081/mm.2008.2599
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of different thresholds for the anti-HIV avidity index

Abstract: INTRODUZIONEUn'analisi accurata dell'epidemia da HIV in atto nel nostro paese si dovrebbe basare sull'incidenza dell'infezione (cioè sul numero di soggetti che hanno sieroconvertito in un determinato intervallo di tempo), che indichi non soltanto la velocità di diffusione del virus ma anche le caratteristiche delle persone che si contagiano al momento attuale. Tuttavia, per conoscere l'incidenza di HIV sono necessari studi di coorte impegnativi, molto costosi e difficilmente applicabili alla popolazione genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…For the AI we estimate the window period associated with a number of different thresholds. A threshold of 0.8 has previously been suggested as a cut-off to classify individuals as recently infected, based on sensitivity and specificity of the biomarker 6 months after the midpoint of the seroconversion interval 8 , 19 . We find such a threshold to be associated with a mean window period of 202 days (95 per cent CrI 174, 245).…”
Section: Discussionmentioning
confidence: 99%
“…For the AI we estimate the window period associated with a number of different thresholds. A threshold of 0.8 has previously been suggested as a cut-off to classify individuals as recently infected, based on sensitivity and specificity of the biomarker 6 months after the midpoint of the seroconversion interval 8 , 19 . We find such a threshold to be associated with a mean window period of 202 days (95 per cent CrI 174, 245).…”
Section: Discussionmentioning
confidence: 99%
“…An avidity index < 0.80 indicated that infection was acquired recently (within the past 6 months); a higher index indicated that infection was acquired earlier (>6 months ago). A cutoff value of 0.80 was used and validated as having 93.0% sensitivity, 98.5% specificity ( 10 ), and >90.0% reproducibility. Avidity results were cross-checked with reported time of migration to assess likely place of exposure.…”
Section: The Studymentioning
confidence: 99%
“…An AI lower than 0.80 was selected to define a recent infection because identified as threshold with the highest accuracy (area under the receiver operating curve: 0.958) corresponding to a sensitivity of 93.0% and a specificity of 98.5% [26]; this threshold was found to be associated with a mean window period of 202 days (standard error: 18.4 days) [27]. …”
Section: Methodsmentioning
confidence: 99%
“…The AI of antibodies is calculated by an automated anti-HIV enzyme immunoassay (EIA), the AxSYM HIV 1/2gO (Abbott Diagnostics Division, Delkenheim, Germany), according to a procedure already described by Selleri [ 23 ]. An AI lower than 0.80 was selected to define a recent infection because identified as threshold with the highest accuracy (area under the receiver operating curve: 0.958) corresponding to a sensitivity of 93.0% and a specificity of 98.5% [ 26 ]; this threshold was found to be associated with a mean window period of 202 days (standard error: 18.4 days) [ 27 ].…”
Section: Methodsmentioning
confidence: 99%